2021
DOI: 10.3390/ma14051159
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Fatigue Crack Growth Behavior of the 2.25Cr1Mo0.25V Steel Welded Joint Used in Hydrogenation Reactors

Abstract: In this work, the fatigue crack growth (FCG) behavior and fatigue damage mechanism of the 2.25Cr1Mo0.25V steel welded joint used in hydrogenation reactors were investigated. The multi-pass welding was carried out to manufacture the welded joint using the combined shielded metal arc welding (SMAW) and submerged automatic arc welding (SAAW) processes. The FCG behavior of different zones in the welded joint, including the base metal (BM), the heat-affected zone (HAZ) and the weld metal (WM), were studied by compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The study of Fatigue Crack Growth (FCG) behavior in welds is of great importance, as it changes along the length of the weld seam due to the different thermal cycles to which the material is subjected. Studies have shown that the FCG rate is higher in the HAZ [35,36]. Investigating the mechanical and fatigue properties of the HAZ of a laser weld is a demanding task, due to the narrowness and heterogeneity of the region [37].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Fatigue Crack Growth (FCG) behavior in welds is of great importance, as it changes along the length of the weld seam due to the different thermal cycles to which the material is subjected. Studies have shown that the FCG rate is higher in the HAZ [35,36]. Investigating the mechanical and fatigue properties of the HAZ of a laser weld is a demanding task, due to the narrowness and heterogeneity of the region [37].…”
Section: Introductionmentioning
confidence: 99%
“…Kuts [7] and Delkhosh [8] established a crack growth calculation model based on the finite element method and Paris' law, and investigated the impact of various welding parameters on the fatigue intensity. Some scholars have investigated the crack extension mechanism in depth from a microscopic perspective to reveal the damage development pattern of welded joints [9,10]. However, it has been difficult to perform microscopic analyses to provide intuitive conclusions regarding fatigue performance.…”
Section: Introductionmentioning
confidence: 99%
“…So far, much work has been performed to investigate the microstructures and tensile properties [ 3 , 4 , 5 , 6 ], reheat cracking behavior [ 7 , 8 ], fatigue behavior [ 9 , 10 ], and hydrogen-induced damage at high temperature [ 11 ] of 2.25Cr1Mo0.25V steel. For instance, Fu et al [ 4 ] and Jiang et al [ 5 ] investigated the influences of different heat treatment processes on the microstructure and mechanical responses of 2.25Cr1Mo0.25V steel.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the weld metal exhibited higher strength but lower toughness than the parent metal, which may be due to the presence of more carbides and inclusions in weld. Our recent work investigated the fatigue crack growth behaviors of different zones (i.e., parent metal, heat affected zone, and weld metal) in an as-received 2.25Cr1Mo0.25V steel weldment [ 10 ]. The results showed that the heat-affected zone exhibited a higher fatigue crack growth rate due to non-uniform microstructure with coarse grains, whereas the parent metal showed superior fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%